A theoretical and methodological essay on the concept of vulnerability. - Palacios García, Antonio (Universidad Autónoma de Nuevo León, 2018)
This paper presents a bibliographical review onthe concept and methods of identifying vulnerabilityin urban areas. From systematic bibliographicsearches, the main concepts that orbit around vulnerabilityare defined, as well as their concretionaround the most disadvantaged groups or groupssuch as women, children, the elderly or immigrants.Subsequently, the causes that are usuallypresented to explain the phenomenon and its differentvariants or typologies, environmental, social,economic, residential or subjective, are analyzed.In addition, it also outlines the main methods that,from variables and indices, have been formulatedto try to measure and visualize socio-spatialinequalities in a multidimensional way. Finally,geodemographic analysis is presented as anotherapproach to the analysis of socio-spatial differentiationfrom Sociology and Urban geography.